Influence of product package and quality on purchase decision of fast-moving consumer goods (FMCG) in Lagos state, Nigeria (UNIZIK Journal of Marketing, 2024)
The study examined the influence of product package and quality on purchase decision of Fast-Moving Consumer Goods (FMCG) in Lagos State. The aspects of product package included in the study are colour, labelling, design, and sustainable material. The research design used for the study is explanatory, and a questionnaire was used to collect the data. Cluster sampling was used to divide the population into five administrative divisions and three divisions (Ikeja, Ikorodu and Epe) were randomly selected. Two hundred (200) copies of the questionnaire were administered, and one hundred and twenty-six (126) were retrieved and used for the analysis. The data collected were analysed using frequency distribution, mean, standard deviation and multiple regression. The results indicated an R Square value of 57.3%. The findings showed that colour (b1=0.021, t=0.654, p=0.514˃0.05) does not significantly influence purchase decision, thus disproving the first hypothesis. It was also found that labelling (b2=0.137, t=4.770, p=0.000
Keywords: Package, quality; sustainable material; labelling; FMCG